Locating temporary population centers after an earthquake in urban settlements Case Study: Sabzevar City - javad jamalabadi; mahammad salmanimoghaddam; Ali shekari badi; marzieh Nodeh (تحقیقات کاربردی علوم جغرافیایی)
Temporary resettlement of the population after the earthquake is considered as a pivotal element of crisis management. The selection of suitable centers for the establishment of citizens can have a significant role in rescue and rescue services after the earthquake. The purpose of this study was to identify potential spots for the construction of shelters and temporary accommodation of the population during the occurrence of a possible earthquake. This research is applied in terms of its purpose. The method of study is descriptive-analytical and documentary. Firstly, using the Delphi method, 16 main and effective criteria for locating these centers were identified in the framework of six clusters including access to the communication network, natural features, spatial characteristics, consistent uses, risk management and demographic performance. Then, using the experts' opinions and the network analysis process, the final weight of each criterion was determined. The most important parameters in this research are population density indexes, grade 1 arterial pathways, and suitable area. Finally, by combining the layers of all indicators, a map of the temporary population settlements was prepared in Sabzevar city. The results of the research show that the lack of suitable spaces, including parks and open spaces for temporary accommodation of citizens in Sabzevar city, is quite evident. At the same time, the points of the city, which have adequate open spaces and are compatible with the surrounding land uses, have a relatively better potential for deployment. Accordingly, the best places for temporary accommodation of the population after the earthquake in Sabzevar, including the Eram Park in the north, Imam Reza Park and the Football Stadium in Southeastern City, Shahr-e Basi, National Park and Shariati Conservatory in the city center, tourist hostel, Green spaces and sports grounds in the west, and finally technical and vocational schools in the city of Tohid. In order to improve the conditions in the aftermath of the earthquake, some suggestions are presented in this study.